Cost-Benefit Analysis of Different Pruning Intensities in Guava (Psidium guajava L.) cv. Lucknow-49 - Abhishek Sonkar,; Bhanu Pratap,; Niranjan Singh,; Ashish Kumar Singh,; Hemant Kumar, (The Bioscan, 2025)
he present investigation entitled “Cost-Benefit Analysis of Different Pruning Intensities in Guava (Psidium guajava L.) cv. Lucknow-49” was carried out during the year 2023-2025 at Govind Nagar Farm, Department of Fruit Science, College of Horticulture & Forestry, A.N.D.U.A.&T., Narendra Nagar (Kumarganj), Ayodhya, Uttar Pradesh, India (Lat 26.51° Long 81.78°). This study was conducted to analyze the cost of cultivation and returns per hectare for guava fruit production.